Self-Care and Mental Health Among College Students During the COVID-19 Pandemic: Social and Physical Environment Features of Interactions Which Impact Meaningfulness and Mitigate Loneliness - Barankevich, Ruth; Loebach, Janet (Frontiers in Psychology, 2022)
The Covid-19 pandemic has interrupted patterns and limited opportunities for social interaction, which increased already high loneliness rates among college students. Meaningful social interactions can mitigate negative mental health outcomes such as loneliness and bolster social support, which is in turn linked to better self-care practices. Social connection can aid in self-care through social support as well as be considered a self-care practice itself to counter the negative effects of loneliness. This study examined the social interaction patterns of 132 college students from a mid-sized US university during the pandemic to understand which characteristics support meaningful interactions. Students completed an online survey from October through December 2020 to report details of their 2020 and 2019 social interactions, as well as their most recent interactions, including time spent, the mode (in-person versus virtual), their relationship to others in the interaction, the type of activity and privacy of the setting. Results found that students spent significantly less time interacting with non-roommates in-person in 2020, and more time in voice and video calls. No differences were found for texting and in-person roommate interactions. Meaningfulness was significantly higher for interactions with family or friends. Students reported the highest meaning for interactions that were planned and in-person, with lowest meaning for planned virtual interactions. No differences were observed for meaningfulness based on the type of interaction activity or privacy of the setting. Understanding the characteristics of the most meaningful interactions can help college students prioritize social interactions that may best promote self-care, mitigate loneliness, and bolster social support. High meaningfulness scores for planned in-person interactions suggests that these types of interactions may be most valuable for maintaining existing self-care patterns, engaging in self-care activities, and receiving support. Self-care activities for college students, including social interactions, were significantly impacted by the Covid-19 pandemic, which may have further exacerbated loneliness. College students should be encouraged to consciously engage in person with family and friends to practice self-care and maintain or improve mental health. Strategically selecting interactions that will optimize meaningfulness may therefore be critical to helping students to maintain positive mental health during and beyond the pandemic.